The Impact of Computers on the Legal Profession - John D. Randall (Washington University Law Quarterly, 1977)
The organized bar should aggressively promote continuing education for computer research and discourage the conversion of law libraries to data banks. The social value of our profession depends on the freedom of individual, family lawyers. Their freedom must be ensured by securing for them the same benefits of computer research available to the state employed lawyer and the members of large firms. In this Article, John Randall examines the effect of computers in the age of information on the legal profession. Computer research will enable lawyers to devote less time to research and more to public service projects. Nevertheless, unless lawyers closely monitor the application of computers to legal research—i.e., promote continuing education in computer research and discourage the conversion of law libraries to data banks—the environment in which lawyers work will inevitably be transformed. Only large law firms will be able to absorb the high fixed cost of computer facilities and thus the family lawyer may be forced out of the profession entirely.
Keywords: Computing and the Law